2010
DOI: 10.1007/s00449-010-0415-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shear stress on the microalgae Chaetoceros muelleri

Abstract: The effect of shear stress on the viability of Chaetoceros muelleri was studied using a combination of a rheometer and dedicated shearing devices. Different levels of shear stress were applied by varying the shear rates and the medium viscosities. It was possible to quantify the effect of shear stress over a wide range, whilst preserving laminar flow conditions through the use of a thickening agent. The threshold value at which the viability of algae was negatively influenced was between 1 and 1.3 Pa. Beyond t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 36 publications
1
49
0
7
Order By: Relevance
“…Another study examined the passage of two diatom species through pumps and valves and concluded that the extent of cellular damage was related to operational parameters, such as Review Hildebrand, Davis, Smith, Traller & Abbriano the pressure drop and the rotational speed of the pump [153]. Cultivation in our laboratory has revealed that some species are impervious to highly turbulent mixing, whereas others are sensitive to modest agitation, suggesting that species-specific differences need to be taken into account with regard to shear stress; such differences have also been reported in the literature [150,154]. The data suggests that the issue is not with diatoms as a class, but particular diatom species subjected to particular turbulence conditions.…”
Section: Settling Rates Flocculation Harvesting and Shear Stresssupporting
confidence: 65%
“…Another study examined the passage of two diatom species through pumps and valves and concluded that the extent of cellular damage was related to operational parameters, such as Review Hildebrand, Davis, Smith, Traller & Abbriano the pressure drop and the rotational speed of the pump [153]. Cultivation in our laboratory has revealed that some species are impervious to highly turbulent mixing, whereas others are sensitive to modest agitation, suggesting that species-specific differences need to be taken into account with regard to shear stress; such differences have also been reported in the literature [150,154]. The data suggests that the issue is not with diatoms as a class, but particular diatom species subjected to particular turbulence conditions.…”
Section: Settling Rates Flocculation Harvesting and Shear Stresssupporting
confidence: 65%
“…The algal cell breakage fractions were informed estimates made by extrapolating experimental data summarized in Voutchkov [12]. However, algal cell breakage behavior is influenced not only by operational practices (shear in pumps or valves, transmembrane pressure), but also algal cell type and species (diatom or dinoflagellates) and other biotic factors such as cell age [71][72][73][74][75][76][77]. We reduced this high uncertainty in our model by structuring the distribution of breakage coefficients to encompass a relatively large range, and by incorporating uniform probability distributions for selecting breakage coefficients during each simulation.…”
Section: Uncertainty and Variabilitymentioning
confidence: 99%
“…Los diámetros seleccionados de las mangueras son % in (6,35mm) El número de Reynolds y velocidad de deformación de cizalla para un diámetro de 1/4 in son ba jos en comparación con la investigación realizada por Michels (2010) en la que se presentó muerte celular por fuerza de cizalla a números de Reynolds entre 9,3E3 y 2,3E4. Por otro lado, la velocidad de deformación dependerá de las condiciones en las cuales se trabaje la microalga; de acuerdo con esto se encontraron valores de 2,2 s-1 a 22 s-1.…”
Section: Propuestas De Diseñounclassified